Cohort study protocol of the Brazilian collaborative research network on COVID-19: strengthening WHO global data. Issue 11 (2nd November 2022) - Anschau, Fernando; Aredes, Natália Del' Angelo; Reveiz, Ludovic; Padilla, Monica; Gomes, Rosane de Mendonça; Carvalho, Wellington Mendes; Leles, Fernando Antonio Gomes; Reese, Fernanda Baeumle; Hubert, André Hostílio; Kemper, Elisandréa Sguario; de Souza, Renilson Rehem; Salviano, Cristiane Feitosa; et al.
Abstract : Introduction: With the COVID-19 pandemic, hospitals in low-income countries were faced with a triple challenge. First, a large number of patients required hospitalisation because of the infection's more severe symptoms. Second, there was a lack of systematic and broad testing policies for early identification of cases. Third, there were weaknesses in the integration of information systems, which led to the need to search for available information from the hospital information systems. Accordingly, it is also important to state that relevant aspects of COVID-19's natural history had not yet been fully clarified. The aim of this research protocol is to present the strategies of a Brazilian network of hospitals to perform systematised data collection on COVID-19 through the WHO platform. Methods and analysis: This is a multicentre project among Brazilian hospitals to provide data on COVID-19 through the WHO global platform, which integrates patient care information from different countries. From October 2020 to March 2021, a committee worked on defining a flowchart for this platform, specifying the variables of interest, data extraction standardisation and analysis. Ethics and dissemination: This protocol was approved by the Research Ethics Committee (CEP) of the Research Coordinating Center of Brazil (CEP of the Hospital Nossa Senhora da Conceicao), on 29 January 2021, under approval No. 4.515.519 and by the National Research Ethics Commission (CONEP), on 5 February 2021, under approval No. 4.526.456. The project results will be explained in WHO reports and published in international peer-reviewed journals, and summaries will be provided to the funders of the study.